2017
DOI: 10.22492/ije.5.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging at School: Defining Attributes, Determinants, and Sustaining Strategies

Abstract: Building and sustaining students' sense of belonging at school has been proposed by teachers and researchers as a means of stimulating students' intent or desire to learn and of reducing student attrition. This article will present the results of an inquiry into the literature on belonging to support the perspective that is it necessary, not only to foster a strong sense of belonging, but also to place much greater emphasis on school belonging in educational programs, practices, and research. The aims of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 35 publications
2
32
0
2
Order By: Relevance
“…In a similar vein, Levett-Jones et al (14) showed that the improvement of communication skills had a positive impact on nursing students' sense of belonging. Moreover, in consistent with the current study, previous research applying different methods was successful to enhance sense of belonging (21,27,28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a similar vein, Levett-Jones et al (14) showed that the improvement of communication skills had a positive impact on nursing students' sense of belonging. Moreover, in consistent with the current study, previous research applying different methods was successful to enhance sense of belonging (21,27,28).…”
Section: Discussionsupporting
confidence: 91%
“…Only some studies with other interventional techniques and various sample size measured interventional effect on sense of belonging in the academic environment. Borzabadi and Araghieh (2015) in their study indicated that students' sense of belonging in schools increased by encouraging and motivating them to have this sense (27). In the study of Abolqasemi et al (36), the use of the Jigsaw collaborative learning method had a significant positive effect on increasing sense of belongingness among students and enhancing their social interactions.…”
Section: Discussionmentioning
confidence: 95%
“…Caring teachers engage students in dialogue about their interests and needs, listen attentively, and express empathy (Noddings, 1984(Noddings, , 2005Osterman, 2010). Teachers further demonstrate authentic care by using positive and respectful communication (Ginot, 1972;Marshall, 2012), fostering peer discussion and interactions (Keyes, 2019;Osterman, 2010;St-Amand, Girard, & Smith, 2017), and using a familial approach to maximize each student's potential (Pang, Rivera, & Mora, 2000).…”
Section: The Ethics Of Care: a Relational Approach To Schoolingmentioning
confidence: 99%
“…The relational bonds that grow from authentic care are vital to students' sense of belonging (Allen, Kern, Vella-Brodrick, Hattie, & Waters, 2018;Keyes, 2019;Osterman, 2000;Riley, 2019;St-Amand et al, 2017;Wang & Eccles, 2012). However, Noddings (2005) observes that, "in many of our schools today, we find teachers are trying to care and students who want to be cared for, and yet many of those students claim, 'Nobody cares!'…”
Section: Challenges To Authentic Care and Belonging In Schoolsmentioning
confidence: 99%
“…Okulun bir üyesi olarak değerli olduğunu düşünmeyi okula ait olma duygusunun temeli olduğunu ifade eden araştırmacılar, bu kavramı öğretmen öğrenci ilişkisi ile bağlantılı olarak görmüşlerdir (Juvonen, 2006). Yapılan araştırmalarda öğretmen ve öğrenciler arasındaki ilişki nitelikli bir şekilde devam ettiğinde öğrencilerin okula aidiyet duygularının geliştiği ve okula bağlandıkları görülmüştür (St-Amand, Girard ve Smith, 2017;Can, 2014;Cremmers ve Kyriakides, 2008). Dilekmen (2008) tarafından etkili bir ilişki kurmada kullandığı öğretmen davranışlarının ne olduğuna dair literatür taraması yaptığı araştırmasında öğrencilerin sorunlarıyla ilgilenme, gelişimlerini destekleme, onları motive etme, duygularını anlama, özgüvenini destekleme, iş birliğine dayalı bir ortam hazırlama ve olumlu bir çevre kurma konusunda yardım etme gibi tutum ve davranışları sıralamıştır.…”
Section: Tartışma Ve öNerilerunclassified